Home delivery among antenatal care booked women in their last pregnancy and associated factors: community-based cross sectional study in Debremarkos town, North West Ethiopia, January 2016 - Habtamu Kebebe Kasaye; Zerfu Mulaw Endale; Temesgen Worku Gudayu; Melese Siyoum Desta (BMC, 2017)
Abstract Background In Ethiopia, nearly half of the mothers who were booked for antenatal care, who supposed to have institutional delivery, gave home delivery nationally. Home delivery accounts majority while few of childbirth were attended by the skilled provider in Amhara regional state. This study aimed to determine the proportion of home delivery and associated factors among antenatal care booked women who gave childbirth in the past 1 year in Debremarkos Town, Northwest Ethiopia. Methods A community-based Cross sectional study was conducted from January 1st− 25th 2016. Epi Info version 7 was used to determine a total sample size of 518 and simple random sampling procedure was employed. Data was collected through an interview by using pretested structured questionnaire. Data were entered into Epi Info version 7, cleaned and exported to SPSS version 21 for analysis. A p-value less than or equals to 0.05 at 95% Confidence Intervals of odds ratio were taken as significance level in the multivariable model. Results A total of 127 (25.3%) women gave childbirth at home. Un-attending formal education (Adjusted Odds Ratio = 7.56, 95% CI: [3.28, 17.44]), absence of health facility within 30 min distance (AOR = 3.41, 95% CI: [1.42, 8.20]), not exposed to media (AOR = 4.46, 95% CI: [2.09, 9.49]), Unplanned pregnancy (AOR = 3.47, 95% CI [1.82, 6.61]), attending ANC at health post (AOR = 5.45, 95% CI: (1.21, 24.49) and health center (AOR = 2.74, 95% CI [1.29, 5.82]), perceived privacy during ANC (AOR = 3.69[1.25, 10.91]) and less than four times ANC visit (AOR = 5.04, 95% CI (2.30, 11.04]) were significantly associated with home delivery. Conclusions Home delivery in this study was found to be low. Educational level, media exposure, geographic access to a health facility, Unplanned pregnancy, an institution where ANC was booked, perceived privacy during ANC and number of ANC visit were found to be determinants of home delivery. Health institutions, health professionals, policy makers, community leaders and all concerned with the planning and implementation of maternity care in Ethiopia need to consider these associations in implementing services and providing care, for pregnant women.